Screening for malnutrition among nursing home residents - a comparative analysis of the Mini Nutritional Assessment, the Nutritional Risk Screening, and the Malnutrition Universal Screening Tool - Diekmann, Rebecca; Winning, Katrin; Uter, Wolfgang; Kaiser, Matthias; Sieber, Cornel; Volkert, Dorothee; Bauer, Jürgen (Journal of Nutrition, Health & Aging, 2013)
The European Society for Clinical Nutrition and Metabolism (ESPEN) has recommended the Mini Nutritional Assessment (MNAA (R)), the Nutritional Risk Screening 2002 (NRS), and the Malnutrition Universal Screening Tool (MUST) for nutritional screening in various settings and age groups. While in recent years all three tools have been applied to nursing home residents, there is still no consensus on the most appropriate screening tool in this specific setting.The present study aims at comparing the MNA, the NRS, and the MUST with regard to applicability, categorization of nutritional status, and predictive value in the nursing home setting.MNA, NRS, and MUST were performed on 200 residents from two municipal nursing homes in Nuremberg, Germany. Follow-up data on infection, hospitalization, and mortality were collected after six and again after twelve months.Among 200 residents (mean age 85.5 +/- 7.8 years) the MNA could be completed in 188 (94.0%) and the NRS and MUST in 198 (99.0%) residents. The prevalence of 'malnutrition' according to the MNA was 15.4%. The prevalence of 'risk of malnutrition' (NRS) and 'high risk of malnutrition' (MUST), respectively, was 8.6% for both tools. The individual categorization of nutritional status showed poor agreement between NRS and MUST on the one hand and MNA on the other. For all tools a significant association between nutritional status and mortality was demonstrated during follow-up as classification in 'malnourished', respectively 'high risk of malnutrition' or 'nutritional risk', was significantly associated with increased hazard ratios. However, the MNA showed the best predictive value for survival among well-nourished residents.The evaluation of nutritional status in nursing home residents by MNA, NRS, and MUST shows significant differences. This observation may be of clinical relevance as nutritional intervention is usually based on screening results. As the items of the MNA reflect particularities of the nursing home population, this tool currently appears to be the most suitable one in this setting.
Keywords: Malnutrition; screening tool; nursing home; nutrition; outcome